Technology Training : Utilizing GeoGebra in Mathematics Learning - R, Zubaidah; Pasaribu, Revi Lestari; Dona Fitriawan; Ade Mirza; Dede Suratman; Edy Yusmin; Dian Ahmad; Rustam; Nadya Febriani Meldi; Metia Novianti; Agus Winarji (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service Activity began with a discussion between the mathematics education study program lecturers, the faculty of teaching and educational sciences at Tanjungpura University, and the chairman of the Kubu Raya Subject Teachers' Conference about the rapid development of technology, especially in mathematics learning. Through this discussion, it was found that many teachers still need to utilize technology in teaching mathematics. One technology that is often used in mathematics learning is GeoGebra. GeoGebra is an application with various features that can be used to explain concepts and numbers in mathematics learning, such as plane geometry, space geometry, algebra, etc. Therefore, teachers need technology-related training to assist in learning, especially GeoGebra. Mastery of this technology is an unavoidable demand, and it also plays a role in improving education in Indonesia, especially in West Kalimantan. This training was held on 8 August 2024, with a total of forty-five participants consisting of thirty-five mathematics teachers from various junior high schools in Kubu Raya, three mathematics education students, and seven lecturers at the Tanjungpura University mathematics education study program. This training aims to increase teachers' motivation and ability to use GeoGebra in mathematics learning. The outputs produced in this activity are 1) implementation of training, 2) publication of documentary video activities on social media, and 3) activity reports.